2011
DOI: 10.2135/cropsci2010.12.0728
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Normalized Difference Vegetation Index and Visual Quality in Cool‐Season Turfgrass: I. Variation among Species and Cultivars

Abstract: Canopy spectrai reflectance may provide an objective means to evaluate visual quality of turfgrass, but evaluations of visual quality may be confounded by differences in reflectance among species or cultivars. In this 3-yr study near Manhattan, KS, we examined effects of species and cultivars on relationships between normalized difference vegetation index (NDVI) and visual quality ratings in Kentucky bluegrass {Poa pratensis L., 'Apollo'), two Kentucky bluegrass x Texas biuegrass {Poa arachnifera Ton.) hybrids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
28
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 22 publications
6
28
1
Order By: Relevance
“…These findings with NDVI also demonstrated the importance of combining correlation analysis with ANOVA in evaluating objective color parameters. Previous reports by Bremer et al (2011aBremer et al ( , 2011b also indicated the limitations and species dependence of predicting turf quality based on NDVI.…”
Section: Nitrogen Fertility In Bermudagrass and Creeping Bentgrassmentioning
confidence: 92%
“…These findings with NDVI also demonstrated the importance of combining correlation analysis with ANOVA in evaluating objective color parameters. Previous reports by Bremer et al (2011aBremer et al ( , 2011b also indicated the limitations and species dependence of predicting turf quality based on NDVI.…”
Section: Nitrogen Fertility In Bermudagrass and Creeping Bentgrassmentioning
confidence: 92%
“…Normalized difference vegetative index is a measurement of red and near‐infrared light reflectance and has become the most commonly used vegetation index for agronomic crops and maintained turfgrass (Carrow et al, 2010; Murphy et al, 2014; Rouse et al, 1974). Several factors that contribute to overall turf quality have been associated with this index including color, canopy structure, density, and chlorophyll concentrations (Bremer et al, 2011; Stiegler et al, 2005; Trenholm et al, 1999, 2000). Previous research has shown that chlorophyll concentrations are negatively impacted by drought stress (DaCosta et al, 2004).…”
mentioning
confidence: 99%
“…Reflectance‐based methods are more objective than traditional visual ratings, and the two methods are well correlated (Trenholm et al, 1999; Bell et al, 2009; Bremer et al, 2011a; Schiavon et al, 2011; Rimi et al, 2013; Leinauer et al, 2014). Still, several studies have demonstrated the limitations of replacing visual ratings with reflectance‐based methods.…”
mentioning
confidence: 99%